Time-consistent implementation in macroeconomic games - Jean Barthélémy; Eric Mengus (Theoretical Economics, 2024)
The commitment ability of governments is neither infinite nor zero but intermediate. In this paper, we determine the commitment ability that a government needs to implement a unique equilibrium outcome and rule out self-fulfilling expectations. We show that, in a large class of static macroeconomic games, the government can obtain a unique equilibrium with any low level of commitment ability. We finally derive implications for models of bailouts and capital taxation.
Keywords: C73; E58; E61; G28; 330; Implementation; limited commitment; policy rules